A Study on Factors Affecting High Quality Fruit Tomato Production in a Greenhouse by Utilizing Low Cost Smart Agriculture Framework - Ramadhona Saville; Katsumori Hatanaka; Denis Pastory Rubanga (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2020)
In this paper, we present an examination of factors affecting the sweetness degree of fruit tomato by utilizing a low-cost smart agriculture framework. Japanese consumers are willing to pay a sky-high price for particularly high sweetness degree of tomato, known as fruit tomato. Japanese farmers would like to produce sustainable fruit tomato, yet only some of the veteran farmers with tens of years of experience or big industrialized farms can produce it. Small scale farmers still struggle to produce sustainable fruit tomato. Many of them would like to know what factors affecting the sweetness degree of tomato. This study aims to clarify factors affecting the sweetness degree production by using a low-cost smart agriculture framework installed in a fruit tomato farmer in Nara prefecture, a western part of Japan. The data used were automatic data gathered from the sensor network, i.e. temperature, humidity, atmospheric pressure as well as CO2; and manually input cultivation records, namely, fertilizers (Ca, NO3), pH, EC (electrical conductivity), harvesting record (yield and sweetness degree) as well as cropping calendar. We gathered data from June 2017 to December 2019. We then conducted a statistical analysis using the R statistical computing language. We found that the most significant factor for a high sweetness degree of fruit tomato is the growing time, that is the longer the growing time, the higher the sweetness degree of fruit tomato. The growing time is likely to be affected by season, as in summer growing time is faster than in wintertime. Consequently, summer is not the best time to grow fruit tomato.